Crosstalk between microRNA-122 and FOX family genes in HepG2 cells. Issue 4 (February 2017) - Kumar, Subodh; Batra, Ankita; Kanthaje, Shruthi; Ghosh, Sujata; Chakraborti, Anuradha
MicroRNA-122 (miR-122) is liver specific and plays an important role in physiology as well as diseases including hepatocellular carcinoma (HCC). Downregulation of miR-122 in HCC modulates apoptosis. Similarly, the putative targets of miR-122, the forkhead box (FOX) family genes also play an important role in the regulation of apoptosis. Hence, an interplay between miR-122 and FOX family genes has been explored in this study. Initially, an augmentation of apoptosis was noticed in HepG2 cells after transfection with miR-122. Further, the predicted miR-122 targets, the FOX family genes ( FOXM1b, FOXP1, and FOXO4) were selected via in silico analysis based on their role in apoptosis. We checked the expression of all these genes at transcript level after the transfection of miR-122 and found that the relative expression of FOXP1 and FOXM1b was significantly downregulated (p < 0.005) and that of FOXO4 was upregulated (p < 0.005). Thus, the finding indicates deregulation of these FOX genes as a result of miR-122 augmentation might be involved in the modulation of apoptosis. Impact Statement: Here, we have investigated the crosstalk between microRNA-122 (miR-122) and selective FOX family genes in HepG2 cells. miR-122 is a prominent miRNA in liver and has been reported to be downregulated in hepatocellular carcinoma (HCC). It has been speculated that diminished level of miR-122 during HCC might be one of the reasons for tumor progression. However, the exact molecular interactions are not clear yet. This study unravels one of the molecular mechanisms of miR-122 through which it might impact the tumorigenesis of HCC.